If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+1/3=x-1
We move all terms to the left:
2x+1/3-(x-1)=0
We get rid of parentheses
2x-x+1+1/3=0
We multiply all the terms by the denominator
2x*3-x*3+1+1*3=0
We add all the numbers together, and all the variables
2x*3-x*3+4=0
Wy multiply elements
6x-3x+4=0
We add all the numbers together, and all the variables
3x+4=0
We move all terms containing x to the left, all other terms to the right
3x=-4
x=-4/3
x=-1+1/3
| 10x+19x-26=90 | | 257-x=172 | | 1.1x-5.4=-10 | | -14x-126+5x=207 | | .75x-6.5=10 | | |4b-4|+|3-b2|+2b3b=2 | | x+3x=2x-12 | | v-8.76=3.98 | | 1/6(7x-4)=x+4/12 | | Y=10000-250x^2 | | -160=8(1+7x) | | 6z+5(-2z-7)=z-1 | | 0.08(y-4)+0.16y=0.20y-0.3 | | 3/4x-61/2=10 | | -n/1.3=8.3 | | 9x-38+4x+23=180 | | Y÷7=q | | 11-4x+15=6 | | 3z=2z-1 | | x/6+7=0 | | 3k-5=5-8k | | 2.5/6=h/9= | | 10x-+2(1-x)=6 | | 10x-2(1-x)=6 | | 11/6=n | | (D^4+4D^3+8D^2+4)y=0 | | 4(a-3)=8a-(4+12) | | 7/2x+112=-59 | | -8k=-56 | | 11=-15x+2 | | 3x+116=4x-6x | | y+(10)=36 |